The Virtues of Humility and Reverence as Foundations of Spiritual Leadership - Philippe JACQUINOT1; Arnaud PELLISSIER-TANON2 (Communications of International Proceedings, 2025)
This reflection aims to deepen our understanding of the role of the virtues of humility and reverence within the field of spiritual leadership. While humility, already well studied, fosters trust and cooperation by limiting ego and valuing others, reverence—understood as conscious respect for a higher order—remains underexplored in management sciences. We hypothesize that the combination of these two virtues can enhance employees’ commitment to a business project grounded in a transcendent vision. This dual disposition sheds new light on Fry’s (2003) model of spiritual leadership by articulating a personal ethical posture (humility) with an orientation toward a higher purpose (reverence). This articulation is particularly meaningful in the Christian tradition, where humility is conceived as recognition of one’s condition as a creature, and reverence as respect for God, others, and Creation. It invites us to consider the leader as the bearer of an ethical and meaningful project, in the service of the common good.
Keywords: Humility; organizational commitment; reverence; spiritual leadership; transcendence.